Računalniške tehnologije za prevajanje - Vintar, Špela (Uporabna informatika (Ljubljana), 1999)
To a technologically aware translator a computer is more then simply a typewriter. Tools for Computer-assisted-Translation - an umbrella term embracing spellcheckers, on-line dictionaries and thesauri as well as Translation Memory and Terminology Management systems - have the potential to raise the quality, speed and cost effectiveness of the translation process. Itis also undergoing profound changes due to the explosive growth of the Internet. The paper gives an overview of translaton technologies and resourcesfrom their beginnings in machine translaton to the software products development during the past few years. Described are applications of textual corpora in translation and the impact of new information and communication media in this field. The concluding section outlines the present situation in Slovenia and suggests ways for further implementation of translation technologies, especially by (re-)designing translator-training curricula.
Keywords: prevajanje; računalniška lingvistika